Performance of vertical subsurface flow constructed wetland with limestone filter for leachate treatment - Noraini, Ibrahim (2013)
Nowadays, the solid waste produced is increasing at high rate and known as global environmental issue as well as in Malaysia and the most common practice to reduce and dispose them is by using landfill method. However, landfill can causes generation of leachate. Leachate is highly contaminated since it contained high level of organic and inorganic matters. Before discharge to water body, leachate needs to be treated. This study was focused on the performance of constructed wetland and limestone filter in treating leachate. Constructed wetland and limestone filter emerged as one of the potential treatment to remove contaminants from leachate. In this study, limestone size from 2mm to 14mm was used for limestone filter and constructed wetland developed by using aggregate size from 5mm to 20mm, sand and planted with Typha Latjfolia (Cattails) to treat landfill leachate. Leachate was collected from Jerangau-Jabor Landfill. Different flowrate (3LPM and 4LPM) was studied to compare the efficiencies of the treatment system in term of pollutants removal in leachate. The treated leachate was analyzed for BOD, COD, TSS, pH, oil and grease, and metals removal such as lead(Pb), copper(Cu), iron(Fe), zinc(Zn), manganese(Mn) and nickel(Ni). The treatment system with two variation flowrate showed effectiveness to remove the parameter but treatment with flowrate 3LPM showed more removal since the contact time taken was longer than 4LPM. Only TSS, COD andoil and grease succeed comply the standard after the treatment with 46mg/L and 1 .63mg/L respectively. Parameter of BOD, NH3 -N, Pb and Mn showed removal at the end of treatment but still not comply the standard. Metals such as Cu, Fe, Zn and Ni already comply standard and still have removal after treatment. The pH of leachate before and after treatment was satisfy the standard from 6-9. This is because the treatment does not affect the pH value in a leachate wastewater.